Deliverable Factors of Manpower Requirement Plan: An Evidence from Indian EPC Company - Amruth S. Gurudev; Srinivasa Rao Potti; Shiva H.C. Prasad (International Journal of Engineering and Technology, 2017)
This paper discusses the manpower plan required, and their deliverables factors to the clients of an Engineering Procurement and Construction in the process of designing for the construction of a thermal power plant, analyses the resource usage versus the planned allocated scheduled resources, resource levelling of scheduling. As a part of resource availability constraints in a critical path, method calendars were used to postpone activity start time, extend the activity duration that resulted in an increase of the project duration. A method of a forward pass has been proposed with the help of the S-curve diagram interpretation with the application of DMADV approach for resource levelling is illustrated with an activity-on-node as a case and a precedence diagram method. This research has elucidated on the critical issues of resource constrained levelling in the application domain of the project management in anticipation of deliverables from its employees to an EPC company. The findings of this research would provide useful inputs for the vendors and the consulting firm.
Keywords: O22; O15; 330; Critical method; Manpower planning; Resource levelling; S-curve